Implementation and Evaluation of the Early-Onset Sepsis Risk Calculator in a High-Risk University Nursery. (August 2018) - Beavers, Jessica B.; Bai, Shasha; Perry, Jennifer; Simpson, Jordan; Peeples, Sara
There is growing interest in the Kaiser early-onset sepsis (EOS) risk calculator though institutions are hesitant to deviate from the Centers for Disease Control and Prevention guidelines and implement this in their hospitals. We describe the process of implementing routine use of the risk calculator in term and late preterm newborns delivered to mothers with chorioamnionitis in a level III neonatal intensive care unit (NICU). A retrospective chart review of infants delivered to mothers with chorioamnionitis from 2011 to 2014 was performed. Implementation of routine use of the calculator began in January 2015; preintervention and postintervention data were analyzed after a 9-month period of routine use. Following implementation, NICU admission rates, number of blood cultures drawn, and rates of antibiotic use dropped by 54%, 42%, and 59%, respectively ( P < .001). No negative outcomes were reported. In this article, we describe how the calculator was safely implemented in our NICU while decreasing the number of interventions.